Effect Of Consuming Omega 6 On Learning Achievement Of Grade 1 Elementary School Students In Coastal And Urban Areas - Nurasmi Nurasmi; Gusriani Gusriani; Rahimah Rahimah (CV. Inara, 2021)
Omega 6 is a group of plural unsaturated fatty acids and includes esential fatty acids because is cannot be producet by the body. The unsaturated chain (doubel bond) in the first omega 6 is found in the 6th carbon chain, and therefore it is called omega 6. Student learning achievements both in coastal and urban areas must be the same. The purpose of this study was to determine the effect of consumption of omega 6 on learning achievements of grade 1 elementary school student in coastal and urban areas. This research used analytical research methods with cross sectional design. The population in this study was all grade 1 elementary school student in SDN 032 Amal Lama with 27 students and all grade 1 students in SDN 015 Kampung Enam with 27 students. Samples were taken using the totality population technique with a total of 54 people. The Chi-Square test obtained the value of P in the coastal area was 0.48, which was < 0.05, and in the urban area was 0.24 which was < 0.05, H0 was rejected and H1 was accepted which mean that there was an influence of omega 6 consumption of omega 6 unsaturated fatty acids was not the only major factor in the effect of learning achievement of grade 1 elementary school children in coastal and urban areas. Other factors such as the environment and education of parents also supported in increasing student achievement and in providing information and knowledge to students.